A high ductility concrete material and its preparation process
By modifying the light-absorbing and high-temperature-resistant modifier on the surface of PVA fibers, the problems of excessive fiber bonding force and poor thermal stability in high-ductile concrete are solved, and the high-temperature and ultraviolet resistance of concrete are significantly improved.
Patent Information
- Application Number
- CN202411069130.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-08-06
AI Technical Summary
In high ductility concrete, the surface bonding force of PVA fibers is too strong, which leads to the fibers being easily pulled out, and the fibers have poor thermal stability and are prone to failure in fires; at the same time, long-term light will destroy the mechanical properties of the concrete.
A cage-type silsesquioxane with high temperature resistance and 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole with high temperature resistance was used to synthesize a light-absorbing high temperature resistance modifier through chemical bonding, and modify it on the surface of PVA fibers to prepare modified PVA fibers.
Modified PVA fibers have significantly improved their high temperature resistance and ultraviolet resistance. The chemical bonding force between the fiber and the concrete matrix is reduced. The fibers are more stable in high temperature and ultraviolet environments, and the mechanical properties of concrete materials have also been improved.
Smart Images

Figure CN118978355B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete material research and development, and in particular to a high-ductility concrete material and a preparation process thereof. Background Art
[0002] As a high-performance fiber (polyethylene, polyvinyl alcohol, polypropylene fiber, etc.) reinforced cement-based material, high-ductility concrete has multi-crack cracking characteristics, strain hardening characteristics and excellent crack control ability. When subjected to bending and tensile loads, due to the bridging effect of the fiber, the cracks can stably expand and show obvious multi-crack cracking characteristics and strain hardening behavior. Compared with traditional concrete, the tensile strain of high-ductility concrete can reach more than 3%, and the crack width is controlled below 100μm. The interfacial bonding performance between the fiber and the matrix determines the macroscopic ductility of high-ductility concrete. According to the fiber bridging theory, under the action of tensile load, the fiber is the carrier of stress transfer in the matrix, transferring the stress at the crack to the surrounding matrix. Therefore, the interfacial bonding between the fiber and the matrix is the key to the high ductility of cement-based composite materials.
[0003] High-strength and high-elastic modulus polyvinyl alcohol (PVA) fibers are often used in high-ductility concrete. However, their surface contains a large number of hydroxyl groups, which leads to excessive interfacial bonding between the fibers and the matrix. The fibers are easily broken during the process of being pulled out of the matrix, limiting the bridging effect of the fibers.
[0004] In addition, the thermal stability of polyvinyl alcohol (PVA) fibers used in high-ductility concrete is poor. When a fire occurs in a building, the relevant mechanical properties of this material may fail due to the melting of internal fibers, and even cause the entire structure to be destroyed. Therefore, it is of great significance to improve the high temperature resistance of polyvinyl alcohol (PVA) fibers.
[0005] In addition, long-term light exposure will destroy the mechanical properties of concrete materials, leading to material aging and performance loss. This is because the ultraviolet rays in the light will enter the pores of concrete through the micro-cracks on the surface of the concrete, accelerating the internal carbonization reaction and causing the calcium carbonate content to increase. The hydration reaction of the concrete is weakened, and expansion stress is generated in the concrete, which ultimately affects its compressive strength and causes the concrete structure to be destroyed. Therefore, it is imperative to carry out anti-ultraviolet modification on concrete materials.
[0006] The present invention cites the following references:
[0007] The doctoral dissertation of Shanghai Jiao Tong University, "Morphological Structure, Shape Memory and Self-Healing Properties of Organic-Inorganic Hybrid Polymers Containing Polyhedral Oligomeric Silsesquioxanes", disclosed the structure and preparation method of 3-hydroxypropylheptaphenyl POSS (POSS-OH). Summary of the invention
[0008] The invention provides a high-ductility concrete material and a preparation process thereof. Cage-type silsesquioxane with a high-temperature resistance function, 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole with a high-temperature resistance and light absorption function, and tetrabutyl titanate with hydrolysis and crosslinking ability are used as raw materials to develop and synthesize a light-absorbing high-temperature resistance modifier. The light-absorbing high-temperature resistance modifier is modified on the surface of a PVA fiber to obtain a PVA fiber with a high-temperature resistance and light absorption function. The PVA fiber is used to improve the performance of the concrete material.
[0009] A preparation process of a high ductility concrete material comprises the following steps:
[0010] Step 1: Prepare a light-absorbing, high-temperature-resistant modifier containing a titanate group, the chemical structure of which is:
[0011]
[0012] Wherein, Ph represents phenyl;
[0013] Step 2: The light-absorbing and high-temperature-resistant modifier prepared in step 1 is subjected to a hydrolysis reaction of the titanate group to obtain a Ti-OH functional group, and the Ti-OH functional group undergoes a dehydration condensation reaction with the -OH functional group carried by the PVA fiber, and the light-absorbing and high-temperature-resistant modifier is modified on the surface of the PVA fiber to prepare a modified PVA fiber;
[0014] Step 3: Add the modified PVA fiber into concrete to prepare a high-ductility concrete material.
[0015] Preferably, the preparation method of the light-absorbing high temperature resistant modifier is:
[0016] Using the nucleophilic substitution reaction mechanism, the hydroxyl functional group of 3-hydroxypropyl heptaphenyl POSS reacts with the chlorine functional group of 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole to generate intermediate 1;
[0017] Intermediate 2 was synthesized by the vertex-opening method using intermediate 1 as a raw material and trifluoromethanesulfonic acid as an opening reagent;
[0018] Intermediate 2 was used as raw material and tetrabutyl titanate was used as a capping agent to synthesize a light-absorbing and high-temperature-resistant modifier through a vertex-capping method.
[0019] Preferably, the formula of the high ductility concrete material is: 400-600 parts by weight of cement, 400-600 parts by weight of fly ash, 300-500 parts by weight of machine-made sand, 100-200 parts by weight of stone powder, 300-500 parts by weight of water, 1-5 parts by weight of water reducer and 20-30 parts by weight of modified PVA fiber.
[0020] Preferably, the modified PVA fiber has a formula in which the mass ratio of the light-absorbing and high-temperature-resistant modifier to the PVA fiber is 1:(0.5-3).
[0021] Preferably, the PVA fiber has a length of 5 to 8 mm and a diameter of 10 to 20 μm.
[0022] Preferably, the preparation method of the modified PVA fiber is: dissolving 1 to 5 parts by weight of a light-absorbing and high-temperature-resistant modifier in a mixed solution of anhydrous ethanol, anhydrous tetrahydrofuran and deionized water, stirring and mixing at room temperature, then adding 0.05 to 0.5 parts by weight of glacial acetic acid and continuing to stir to obtain a modified liquid, then immersing 0.5 to 15 parts by weight of PVA fiber in the modified liquid, and standing at 30 to 50° C. to prepare the modified PVA fiber.
[0023] A high ductility concrete material prepared according to the above process has a peak stress of 5-6MPa, an ultimate tensile strain of 4-5%, a flexural strength of 13-14MPa, and a compressive strength of 47-48MPa.
[0024] Preferably, the compressive strength reduction rate of the high ductility concrete material after ultraviolet irradiation for 240 days is 1.0-1.5%, and the compressive strength reduction rate after high temperature of 400° C. for 1 hour is 8-9%.
[0025] Beneficial effects:
[0026] The present invention uses an organic chemical synthesis method to synthesize a novel light-absorbing and high-temperature resistant modifier, the molecular structure of which includes: a cage-type silsesquioxane containing a metallic titanium element, a benzene ring, a benzotriazole group and a hindered phenol group, which not only exhibits excellent high-temperature resistance, but also has excellent light absorption performance;
[0027] The light-absorbing and high-temperature-resistant modifier is modified on the surface of the PVA fiber by a chemical bonding method to prepare the modified PVA fiber;
[0028] The concrete material modified with modified PVA fiber not only has excellent mechanical properties, but also has excellent high temperature resistance and UV resistance. It is a high-ductility concrete material and can be used in the field of engineering construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the chemical reaction formula of intermediate 1;
[0030] Figure 2 is the chemical structural formula of intermediate 2;
[0031] Figure 3 It is the chemical structural formula of the light-absorbing and high-temperature-resistant modifier;
[0032] Wherein, Ph represents phenyl;
[0033] Figure 4 The performance test results of concrete materials. DETAILED DESCRIPTION
[0034] Experimental example:
[0035] The light-absorbing and high-temperature-resistant modifier is prepared, and the preparation process is as follows:
[0036] (1) Synthesize intermediate 1, whose chemical reaction formula is as follows Figure 1 As shown, the preparation method is as follows: using the nucleophilic substitution reaction mechanism, the hydroxyl functional group of 3-hydroxypropyl heptaphenyl POSS (POSS-OH) reacts with the chlorine functional group of 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole (ultraviolet absorber UV-327) to generate intermediate 1. The specific experimental steps are as follows: under nitrogen protection, 30 mL of anhydrous tetrahydrofuran and 0.1 g of metallic sodium are added to a three-necked flask, the temperature is raised to 40°C, stirring is started, and 50 mL of 3-hydroxypropyl heptaphenyl POSS solution (prepared by 5.1 g of 3-hydroxypropyl heptaphenyl POSS and 50 mL of anhydrous tetrahydrofuran) is added dropwise to the three-necked flask, the temperature is continued to be raised to 70°C and refluxed for reaction for 1 h, and after cooling to room temperature, 10 mL of 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole solution (prepared by 1.8 g of 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole and 10 mL of anhydrous tetrahydrofuran), heated to 60°C and stirred for 6 h, the solvent was removed by rotary evaporation, and the intermediate 1 was obtained after vacuum drying;
[0037] (2) Synthesize intermediate 2, whose chemical structure is as follows Figure 2 As shown, the preparation method is as follows: intermediate 1 is used as a raw material, trifluoromethanesulfonic acid is used as an opening agent, and intermediate 2 is synthesized by a vertex-opening method. The specific experimental steps are as follows: 4.5 g of intermediate 1 is added to a round-bottom flask, 80 mL of dichloromethane and 6.7 g of trifluoromethanesulfonic acid are added thereto in sequence, and the reaction is stirred at room temperature for 0.5 h. After the reaction is completed, it is filtered, 5A molecular sieves are added to absorb and remove residual trifluoromethanesulfonic acid, the solvent is removed by rotary evaporation, and the intermediate 2 is washed with a saturated aqueous solution of diethyl ether, filtered, and vacuum dried to obtain the intermediate 2;
[0038] (3) Synthetic light-absorbing and high temperature-resistant modifier, whose chemical structure is as follows Figure 3As shown, the preparation method is as follows: intermediate 2 is used as a raw material, tetrabutyl titanate is used as a capping agent, and a light-absorbing high-temperature resistant modifier is synthesized by a vertex-capping method. The specific experimental steps are as follows: 3.1 g of intermediate 2 and 50 mL of anhydrous tetrahydrofuran are added to a three-necked flask, stirred at room temperature until completely dissolved under the protection of nitrogen, and then placed in an ice-water bath, 10 mL of tetrabutyl titanate solution (prepared with 0.9 g of tetrabutyl titanate and 10 mL of anhydrous tetrahydrofuran) is slowly added dropwise to the three-necked flask, stirred in an ice-water bath for reaction for 30 min, then the ice-water bath is removed, and the stirring reaction is continued at room temperature for 4 h, the solvent is removed by rotary evaporation, poured into anhydrous acetonitrile, filtered, washed with anhydrous acetonitrile, and vacuum dried to obtain a light-absorbing high-temperature resistant modifier;
[0039] The nuclear magnetic resonance hydrogen spectrum of the light-absorbing high temperature resistant modifier is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.79-0.82 (t, 2H), 0.92-0.96 (t, 3H), 1.31 (s, 9H), 1.39 (s, 9H), 1.43-1.49 (m, 2H), 1.67-1.74(m, 2H), 1.79-1.86(m, 2H), 3.73-3.76(t, 2H), 3.97-4.01(t, 2H), 6.92-7.93(m, 35H).
[0040] Experimental Example 1:
[0041] The modified PVA fiber is prepared by a dehydration condensation reaction of the Ti-OH functional group obtained by the hydrolysis reaction of the titanate group in the light-absorbing and high-temperature-resistant modifier with the -OH functional group on the PVA fiber, and the light-absorbing and high-temperature-resistant modifier is modified on the surface of the PVA fiber to prepare the modified PVA fiber. The specific experimental steps are as follows: 3g of the light-absorbing and high-temperature-resistant modifier, 40mL of anhydrous ethanol, 10mL of anhydrous tetrahydrofuran and 2mL of deionized water are added to a three-necked flask, stirred and mixed at room temperature for 1h, and then 0.1mL of glacial acetic acid is added and stirred for 4h to obtain a modified solution, and then 5g of PVA fiber is immersed in the modified solution, heated to 40°C and allowed to stand for 4h, washed with anhydrous ethanol, and vacuum dried to obtain the modified PVA fiber;
[0042] Among them, PVA fiber was purchased from Changzhou Tianyi Engineering Fiber Co., Ltd., and its performance parameters are shown in Table 1.
[0043] Table 1 Performance test of PVA fiber
[0044]
[0045]
[0046] Experimental Example 2:
[0047] Preparation of high ductility concrete material: prepare the masterbatch according to the formula of high ductility concrete material in Table 2, sprinkle water inside the mixer to slightly moisten it, pour the prepared masterbatch into the mixer and stir for 2 minutes (stirring speed 10r / min), add the formulated amount of water and water reducer after stirring evenly, keep stirring at 10r / min for 5 minutes, wait until a layer of water film appears on the surface of the concrete by naked eyes, evenly add the formulated amount of modified PVA fiber, continue stirring for 4 minutes (stirring speed 20r / min), and obtain the high ductility concrete material;
[0048] According to the formulation in Table 2, referring to the preparation steps and process conditions of the high ductility concrete material, concrete material a and concrete material b were prepared in sequence, which were respectively referred to as comparative examples 1 and 2.
[0049] Table 2 Experimental formula of concrete materials
[0050]
[0051] The specifications and manufacturers of the raw materials used in Example 2 are shown in Table 3;
[0052] Table 3 Experimental raw materials
[0053]
[0054]
[0055] Performance Test:
[0056] (1) Fiber bonding performance test: The modified PVA fiber and the ordinary PVA fiber were respectively pasted on the sample-carrying cuboid using double-sided tape, with a portion of the lower end exposed to be buried in the concrete matrix; the concrete material b was poured into the mold, compacted and smoothed to obtain a concrete matrix; the exposed ends of the modified PVA fiber and the ordinary PVA fiber pasted on the sample-carrying cuboid were respectively inserted vertically into the concrete matrix, and the sample-carrying cuboid was removed to expose the free ends of the fibers; the test was performed using a HY-0580 fiber mechanical properties tester, with the tensile rate controlled at 0.25 μm / s, and the fibers were pulled out of the concrete matrix to obtain load-displacement curves, and the bonding strength and pull-out state of the modified PVA fiber and the ordinary PVA fiber were recorded respectively;
[0057] The bonding strength calculation method is:
[0058] Bond strength (J / m 2 ) = maximum load / (π×fiber diameter×fiber embedding length in concrete matrix);
[0059] The test results are shown in Table 4;
[0060] Table 4 Experimental results of fiber bonding performance
[0061]
[0062] (2) The mixed concrete material was placed into the test mold within 20 minutes and vibrated on a vibration table to make it dense. After the vibration was completed, the surface was wrapped with a plastic film. After 24 hours, the mold was removed and moved to a standard curing box for curing for 28 days. After that, the performance test was carried out. The results are shown in Table 5 and Figure 4 shown.
[0063] Table 5 Performance test results of concrete materials
[0064]
[0065]
[0066] By comprehensively analyzing the above experimental results, the following conclusions can be drawn:
[0067] First: The high-ductility concrete material using modified polyvinyl alcohol (PVA) fibers has achieved beneficial technical effects of significantly improving high temperature resistance and UV resistance;
[0068] Second: Compared with ordinary polyvinyl alcohol (PVA) fibers, the chemical bonding force between the polyvinyl alcohol (PVA) fibers grafted with modifiers on the surface and the concrete matrix interface has achieved a beneficial technical effect of significantly reducing, and it can be completely pulled out of the concrete matrix.
Claims
1. A process for preparing a high ductility concrete material, characterized in that: The following steps are involved: Step 1: Prepare a light-absorbing, high-temperature-resistant modifier containing a titanate group, the chemical structure of which is: Wherein, Ph represents phenyl; Step 2: The light-absorbing and high-temperature-resistant modifier prepared in step 1 is subjected to a hydrolysis reaction of the titanate group to obtain a Ti-OH functional group, and the Ti-OH functional group undergoes a dehydration condensation reaction with the -OH functional group carried by the PVA fiber, and the light-absorbing and high-temperature-resistant modifier is modified on the surface of the PVA fiber to prepare a modified PVA fiber; Step 3: Add the modified PVA fiber into concrete to prepare a high-ductility concrete material.
2. The process for preparing a high ductility concrete material according to claim 1, characterized in that: The preparation method of the light-absorbing high temperature resistant modifier is as follows: Using the nucleophilic substitution reaction mechanism, the hydroxyl functional group of 3-hydroxypropyl heptaphenyl POSS reacts with the chlorine functional group of 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole to generate intermediate 1; Intermediate 2 was synthesized by the vertex-opening method using intermediate 1 as a raw material and trifluoromethanesulfonic acid as an opening reagent; The light-absorbing and high-temperature-resistant modifier was synthesized by the vertex-capping method using intermediate 2 as raw material and tetrabutyl titanate as a capping agent.
3. The process for preparing a high ductility concrete material according to claim 1, characterized in that: The formula of the high-ductility concrete material is: 400-600 parts by weight of cement, 400-600 parts by weight of fly ash, 300-500 parts by weight of machine-made sand, 100-200 parts by weight of stone powder, 300-500 parts by weight of water, 1-5 parts by weight of water reducing agent and 20-30 parts by weight of modified PVA fiber.
4. The process for preparing a high ductility concrete material according to claim 3, characterized in that: The formula of the modified PVA fiber is that the mass ratio of the light-absorbing high-temperature resistant modifier to the PVA fiber is 1: (0.5-3).
5. The process for preparing a high ductility concrete material according to claim 4, characterized in that: The PVA fiber has a length of 5 to 8 mm and a diameter of 10 to 20 μm.
6. The process for preparing a high ductility concrete material according to claim 4, characterized in that: The preparation method of the modified PVA fiber is as follows: 1 to 5 parts by weight of a light-absorbing high-temperature-resistant modifier is dissolved in a mixed solution consisting of anhydrous ethanol, anhydrous tetrahydrofuran and deionized water, and the mixture is stirred and mixed at room temperature, and then 0.05 to 0.5 parts by weight of glacial acetic acid is added and stirred continuously to obtain a modified solution, and then 0.5 to 15 parts by weight of PVA fiber is immersed in the modified solution, and the solution is allowed to stand at 30 to 50° C. to prepare the modified PVA fiber.
7. A high ductility concrete material prepared by the process according to any one of claims 1 to 6, characterized in that: The high-ductility concrete material has a peak stress of 5-6 MPa, an ultimate tensile strain of 4-5%, a flexural strength of 13-14 MPa, and a compressive strength of 47-48 MPa.
8. A high ductility concrete material according to claim 7, characterized in that: The compressive strength reduction rate of the high ductility concrete material after ultraviolet irradiation for 240 days is 1.0-1.5%, and the compressive strength reduction rate after high temperature of 400° C. for 1 hour is 8-9%.
9. Application of the high ductility concrete material according to claim 7 in the field of engineering construction.
Citation Information
Patent Citations
High-ductility concrete and preparation method thereof
CN113880534A